Numeric data in search engine results pages - Rovira, Cristí²fol (Anuario ThinkEPI, 2008)
The numeric data provided by search engine results pages is analyzed using correlation coefficients. The conclusion is that numeric data is reliable for studies that compare or evaluate web sites.
Keywords: Search engines; Reliability of search engines; Inconsistency of search engines; Search results page; Search engines numeric date.